A Portrait in Don Juan: Individualization of Myth and Redemption from Sin: Un retrato en Don Juan: individualización del mito y redención del pecado - Otero Luque, Frank (Studium, 2020)
Abstract. There are many types of artistic representations (theatre, music, opera, ballet, literature, cinema, television, painting, sculpture, etc.) of the legend of Don Juan, i.e. the universal archetype of the seducer who, through deception, conquers a woman and, once she succumbs to his charms, he boasts of his triumph, despises her, and shifts his interest towards another lady. In this work, I compare three of the most famous versions don Juan: The Trickster of Seville and the Stone Guest (1630) by Tirso de Molina, Don Giovanni (1787) by Wolfgang Amadeus Mozart and Lorenzo Da Ponte, and Don Juan Tenorio (1844) by José Zorrilla. The first and third are theatrical pieces, while the second is an opera. The myth of Don Juan is essentially the same in all three, but the message and the moral vary according to the cultural movement the works belong to, namely the Baroque, the Enlightenment and the Romanticism, respectively. Key words: The Trickster of Seville and the Stone Guest, Don Giovanni, Don Juan, Tirso de Molina, Wolfgang Amadeus Mozart, Lorenzo Da Ponte, José Zorrilla, sin, redemption, sociopath. Resumen. Son muchos los tipos de representación artística —teatro, música, ópera, ballet, literatura, cine, televisión, pintura, escultura, etc.— de la leyenda de Don Juan, el arquetipo universal del seductor que, mediante engaños, conquista a una mujer y, una vez que ella sucumbe a sus encantos, se jacta de su triunfo, las desprecia y reenfoca su interés en otras damas. En este trabajo, comparo a tres de los don Juanes más famosos: El burlador de Sevilla y convidado de piedra (1630) de Tirso de Molina, Don Giovanni (1787) de Wolfgang Amadeus Mozart y Lorenzo Da Ponte, y Don Juan Tenorio (1844) de José Zorrilla. La primera y la tercera son piezas teatrales, en tanto que la segunda es una ópera. El mito de Don Juan es, esencialmente, el mismo en estas tres obras, aunque varían el mensaje y la moraleja según el movimiento cultural al que pertenecen: Barroco, Ilustración y Romanticismo, respectivamente. Palabras clave: Burlador de Sevilla, Don Giovanni, Don Juan, Tirso de Molina, Wolfgang Amadeus Mozart, Lorenzo Da Ponte, José Zorrilla, pecado, redención, sociópata.